From a supply to a demand-driven value chain: a transformation strategy to achieve a best-in-class customer service level. Issue 2 (14th February 2011) - Freitas, Junior; Lopes, Tiago; Barreiros, Flavio; Bremer, Carlos
Perdigao is one of the world's greatest food industries dedicated to raising, producing and slaughtering poultry and pork and derivates. The complex value chain until 2003 was a traditional supply-driven, presenting an important opportunity to propose an innovative way to drive its value chain to achieve a best-in-class service level. This case describes the 3-year transformation strategy and process highlights: the proposition to change a traditional supply-driven into a demand-driven value chain; the transformation methodology; the comprehensive use of supply and demand management concepts as well as one of the most complete uses of an advanced planning tool system.